Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Let $(X,\mu)$ be a measure space, and $\mu(X)< + \infty$. Let $f$ be a nonnegative measurable function on $X$ and $E_n = \{x \in X|f(x) \geq n \}$. Then $\int_X f^2d \mu < + \infty$ if and only if $\sum_{n=1}^{\infty} n \mu(E_n) <+\infty$.

Do I have to use simple functions that converge to $f$?

Thanks a lot.

share|cite|improve this question

First we use that $$ \int_X g\,\mathrm d\mu=\int_0^\infty \mu\left(\{g\geq t\}\right)\,\lambda(\mathrm dt) $$ for any non-negative measurable function $g$. Using this with $g=f^2$ we get $$ \int_X f^2\,\mathrm d\mu=\int_0^\infty \mu\left(\{f\geq \sqrt{t}\}\right)\,\lambda(\mathrm dt)=2\int_0^\infty x\cdot \mu\left(\{f\geq x\}\right)\,\lambda(\mathrm dx) $$ by change of variables with $x=\sqrt{t}$.

Now $x\mapsto x\cdot \mu\left(\{f\geq x\}\right)$ is measurable and $x\mapsto \mu\left(\{f\geq x\}\right)$ is decreasing, and so $$ \sum_{n=1}^\infty n\cdot \mu\left(\{f\geq n-1\}\right)1_{(n-1,n]}(x)\geq x\cdot \mu\left(\{f\geq x\}\right)\geq \sum_{n=1}^\infty (n-1)\cdot \mu\left(\{f\geq n\}\right)1_{(n-1,n]}(x) $$ and integrating this with respect to $\lambda$ yields $$ \int_0^\infty x\cdot \mu\left(\{f\geq x\}\right)\,\lambda(\mathrm d x)\leq \sum_{n=1}^\infty \left(\int_0^\infty n\cdot\mu\left(\{f\geq n-1\}\right)1_{(n-1,n]}(x)\,\lambda(\mathrm d x)\right)\\ =\sum_{n=1}^\infty n\cdot\mu\left(\{f\geq n-1\}\right)=\sum_{n=0}^\infty (n+1)\cdot\mu\left(\{f\geq n\}\right). $$ Now this last sum is finite if and only if $\sum_{n=1}^\infty n\cdot\mu\left(\{f\geq n\}\right)<\infty$ (by the limit comparison test).

share|cite|improve this answer
You can show that the last sum is finite iff .... using the limit comparison test. – Amr Nov 22 '12 at 7:25
@Amr: Thank you! – Stefan Hansen Nov 22 '12 at 7:26

Forward direction:

First we note that for all n $E_{n+1} \subset E_{n}$, thus $\mu(E_n-E_{n+1})=\mu(E_{n})-\mu(E_{n+1})$. We also note that $E_n-E_{n+1}=${$x∈ X|n<f(x)\leq n+1$}, thus it follows that $E_1-E_2, E_2-E_3, E_3-E_4,...$ are disjoint measurable sets. Now define a function $g:X→R$, such that $g(x)=n$ if $x\in E_n-E_{n+1}$ and 0 otherwise, it follows easily that $g(x)\leq(f(x))^2$, therefore: $$\int_X g d \mu \leq \int_X f^2d \mu$$ Hence: $$\sum_{n=1}^{\infty} n^2(\mu(E_n)-\mu(E_{n+1})) \leq \int_X f^2d \mu...(1)$$

Now define $h_n(x)=n^2$ if $x\in E_n$ and 0 otherwise. It follows that $h_n \leq f^2$, therefore: $$\int_X h_n d \mu \leq \int_X f^2d \mu$$ Hence, we have for all n: $$n^2\mu(E_n) \leq \int_X f^2d \mu...(2)$$

Now, we use Abel's identity to deduce that: $$\sum_{n=1}^k (n+1/2)\mu(E_{n+1})=(k+1)^2\mu(E_{k+1})/2-\mu(E_1)-\sum_{n=1}^k (n^2/2)(\mu(E_{n+1})-\mu(E_n))$$ From inequalities (1),(2) we find that the R.H.S. of the previous equation is bounded, thus the sequence of partial sums $\sum_{n=1}^k (n+1/2)\mu(E_{n+1})$ is bounded from above, hence it converges. Since, for all n $n/2<n+1/2$, thus we deduce that the sequence $\sum_{n=1}^k (n/2)\mu(E_{n+1})$ converges.

Backward Direction:

Using the limit comparison test, we can show that $\sum_{n=1}^{\infty} (2n+3)\mu(E_{n+1})$ converges. Using Abel's identity we have: $$\sum_{n=1}^k ((n+1)^2)(\mu(E_{n+1}-\mu(E_n)))=(k+2)^2\mu(E_{k+1})/2-4\mu(E_1)-\sum_{n=1}^k (2n+3)\mu(E_{n+1})$$ Since the R.H.S is bounded therefore the series in L.H.S. converges. Now by letting $g(x)=(n+1)^2$ if $x\in E_n-E_{n+1}$ and 0 otherwise we can see that g is integrable. Since $g \leq f$, therefore $f$ is integrable.

share|cite|improve this answer
There is something missing in the backward direction argument I will edit my answer to add it. – Amr Nov 22 '12 at 7:23
I am pretty sure that $\sum (k\mu(E_k))<\infty$ implies that $k^2/mu(E_k)$ is bounded – Amr Nov 22 '12 at 7:28
I am pretty sure that $\sum (k\mu(E_k))<\infty$ implies that $k^2/\mu(E_k)$ is bounded – Amr Nov 22 '12 at 7:35

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.